Is it Better to be Safe than Sorry? The Cartagena Protocol versus the World Trade Organisation - Laidlaw, Anais Kedgley (Victoria University of Wellington Law Review, 2005)
One of the most important developments of the twenty-first century has been the emergence of biotechnology and genetic engineering. In response to this development, the Cartagena Protocol on Biosafety was negotiated, and entered into force in September 2003. The Cartagena Protocol sets up a regime governing the international movement of genetically modified organisms (GMOs) that aims to protect biodiversity from any adverse effects of genetically modified organisms. However, the Cartagena Protocol is not the only regime governing such movement. The World Trade Organisation (WTO) also covers the trade in GMOs, but has a different aim: to prevent limitations on such movement. As a result it is almost inevitable that a dispute concerning the trade in GMOs will occur. Therefore, harmonisation of the two agreements is highly desirable. One way to achieve this, which would then avoid the need for WTO reform, would be for the Cartagena Protocol to be used by the WTO as evidence of internationally accepted standards in relation to GMOs. However, given that the WTO would be unlikely to accept such a proposal, other solutions need to be explored.